2020
DOI: 10.1136/bmjopen-2020-037215
|View full text |Cite
|
Sign up to set email alerts
|

What are the development priorities for management of type 2 diabetes by general practitioners in Ningbo, China: a qualitative study of patients’ and practitioners’ perspectives

Abstract: ObjectivesTo explore patients’ and general practitioners’ (GPs’) perspectives on primary care management of patients with type 2 diabetes mellitus (T2DM) in Ningbo, China. We aimed to understand the current benefits and challenges and to identify development priorities.DesignExploratory qualitative descriptive study using face-to-face interviews and analysed by thematic, inductive analysis.Setting11 primary care facilities spread across the city of Ningbo, China.Participants23 patients with T2DM and 20 GPs inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The experiences of being promoted and linkage between income with CFDS directly satisfied the needs of health workers for career development and increased income, and so these factors could motivate better performance on diabetes care. The finding on the negative impact of higher workload on delivering diabetes management services is in consistent with other findings on the high workload as a demotivation factor [ 16 , 42 ]. The satisfaction on training was found as one important aspect contributing better performance on diabetes management services, which is consistent with previous studies [ 16 , 18 , 19 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…The experiences of being promoted and linkage between income with CFDS directly satisfied the needs of health workers for career development and increased income, and so these factors could motivate better performance on diabetes care. The finding on the negative impact of higher workload on delivering diabetes management services is in consistent with other findings on the high workload as a demotivation factor [ 16 , 42 ]. The satisfaction on training was found as one important aspect contributing better performance on diabetes management services, which is consistent with previous studies [ 16 , 18 , 19 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…13 (Continues) management of T2DM in primary care, including unacceptable variations in care. 26 In our study, the odds of dissatisfaction were higher in physically active people compared to those who were not physically active. The finding is inconsistent with other studies conducted among people with T2DM in China, and they found that those who were doing regular exercise were more satisfied.…”
Section: Discussionmentioning
confidence: 42%
“… 13 , 14 A qualitative study conducted among people with T2DM and general practitioners in Ningbo found several issues related to the diagnosis and management of T2DM in primary care, including unacceptable variations in care. 26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations